Necrologías - Blance de Clayre, Beatrice; Hernández Pérez, Mauro S. (Espacio Tiempo y Forma. Serie I, Prehistoria y Arqueología, 1996)
Soler García, José María (1905-1996); Piggot, Stuart (1910-1996).